TRADITIONS, BELIEFS, AND IDENTITY: CHINESE CULTURE IN FRESH OFF THE BOAT - Ernawati, Asih (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The aim of this research is to identify and interpret signs of Chinese culture as manifested in the character of Jessica Huang. This study utilizes a descriptive qualitative approach. Data were collected through a comprehensive analysis of all 13 episodes from the first season of the series. Using Fiske’s three-level semiotic framework, reality, representation, and ideology, the study examines how cultural signs are encoded through Jessica’s actions, language, clothing, and behavioral traits. Specific attention is given to cultural elements such as traditional utensils, attire, rituals, beliefs, linguistic features, communication styles, and frugality, as portrayed in the episodes. Findings indicate that Jessica Huang embodies both authentic cultural expressions and recurring stereotypes, contributing to a complex portrayal of Chinese culture in the American media landscape. The study underscores the role of television in constructing cultural meaning and demonstrates the value of semiotic analysis in unpacking the layered representations within popular media texts.